El concepto “vida” en la ética kantiana: algunas consecuencias para la bioética - Román Maestre, Begoña (Logos. Anales del Seminario de Metafísica, 2007)
This work has three parts. In the first one, if we use the meaning of life by I. Kant, we explain the moral base of the duty to live and why Kant censures suicide and euthanasia. Secondly, if we use the Kantian moral theory of life we highlight the lacks and contradictions of certain proposals that referring to the principle of autonomy– defend suicide and euthanasia. In the third part, although following Kant’s approach of the value of life, we explore the possibility of defending the legitimacy of suicide and euthanasia.